Dextran sulfate/Triton X two-phase micellar systems as an alternative first purification step for clavulanic acid - Silva, Marcela de Siqueira Cardoso; Ebinuma, Valéria de Carvalho Santos [UNESP]; Lopes, André Moreni; Rangel-Yagui, Carlota de Oliveira (Elsevier, 2015)
The development of efficient and cost-effective downstream processes is essential for any pharmaceutical products. Clavulanic acid (CA) is a ß-lactamic drug used combined with antibiotics to inhibit bacterial resistance mediated by ß-lactamase enzymes. CA industrial purification involves techniques such as liquid–liquid extraction with organic solvents and chromatographic techniques, resulting in low recovery yields. In this way, techniques more suitable for biomolecules such as liquid–liquid extraction based on aqueous two-phase systems, which contains 60–90% of water, are of great interest. In this work, aqueous two-phase micellar systems (ATPMS) formed by the nonionic surfactants Triton X-114 and Triton X-100 in the presence or absence of dextran sulfate (Dx-S) were investigated as a first step of CA purification. The drug was found to be stable in the presence of polymers and surfactants with mass balances higher than 80% for all the conditions evaluated. CA partitioning in ATPMS was investigated in the presence of concentrations of Dx-S lower than 4%, CA partitioned more to micelle-poor phase. However, increasing the polymer concentration (8 and 14%), we observed a phase inversion with both surfactants and the drug partitioned more pronounced to the micelle rich-phase, with partition coefficients up to 1.83 with TX-100. The results show that Dx-S/Triton X systems can be used as a first step of CA extraction and the conditions can be adjusted depending on the subsequent extraction methods.
Keywords: Antibiotics; Clavulanic acid; Liquid–liquid extraction; Purification process; Aqueous two-phase micellar systems; Dextran sulfate